Screening of west nile virus (WNV) in mosquitoes from Kuala Gula Bird Sanctuary, Perak - Maizatul Amira Janil. (2019)
West Nile Virus (WNV) is belongs to family of Flavivirus. This virus is transmitted in sylvatic cycle between wild birds and mosquitoes which served as natural reservoir hosts and primary vectors respectively. Meanwhile, mammals including human and bats are dead-end hosts. Previous study in wild birds, Orang Asli and horses revealed that they were seropositive against WNV in Malaysia. However, this study is a preliminary research since there is no study conducted on the presence of WNV in mosquitoes in Malaysia. Although WNV is not endemic in Malaysia yet, but this virus has become a global threat of public health and mosquitoes are abundance in this country. Therefore, objectives of this study are to screen the presence of WNV in mosquitoes in Kuala Gula by using molecular detection methods and to identify the species of mosquitoes that harbour WNV in Kuala Gula, Perak. Convenient sampling was performed by placing mosquito trap in Kuala Gula Bird Sanctuary, Perak. 30 pooled samples were homogenised and extracted according to manufacturer’s guideline. One step RT-PCR targeting highly conserved gene between capsid and pre-membrane revealed that none sample was positive. As a conclusion, this study indicate that there is absence of WNV in 30 pooled samples of mosquito which are Culex (Culex) tritaeniorhynchus, Culex (Culex) vishnui and Culex (Culex) pseudovishnui.